Trichotillomania Symptoms in African American Women: Are they Related to Anxiety and Culture? - Neal‐Barnett, Angela (CNS Neurosci Ther, 2010)
Trichotillomania (TTM) is a little understood disorder that has been underresearched in the African American community. Furthermore, the incorporation of cultural factors into TTM research has virtually been ignored. Existing data from an African American college student population suggest TTM is associated with high levels of anxiety. In this study, we explored anxiety symptoms and cultural hair messages in an African American female community sample with TTM symptoms. We predicted high levels of TTM severity and impairment would be associated with high level of anxiety symptoms. We also predicted that cultural messages about hair will influence both TTM and anxiety symptoms. In this telephone study, 41 African American females participated in interviews about their TTM. TTM impairment and severity was positively correlated with general anxiety symptoms as measured on the Symptom Checklist 90‐Revised (SCL 90‐R(®)). Severity was also positively correlated with obsessive–compulsive symptoms. Given the significance of hair for African American women, we also explored the childhood cultural messages receive about hair. Over half the sample received at least one cultural message about hair. Although many women received the same message, the value they placed on the message differed. Messages received about hair were not associated with TTM severity or impairment. The association among obsessive–compulsive symptoms and hair messages approached significance. Results highlight the importance of assessing anxiety comorbidity and culture with African American TTM samples. Little is known about TTM in African American samples. Existing research indicates this population seeks TTM help from their hairdressers. Among college students, a significant correlation has been found for anxiety as measured on the Beck Anxiety Inventory and TTM. To the best of our knowledge, this is the first paper to examine cultural messages about hair in an African American sample. In addition, rather than looking at college students, this research is conducted with a community sample of mostly professional African American women. The use of the SCL‐90‐R(®) specific anxiety dimensions demonstrates the relationship with TTM severity and impairment.